2006
DOI: 10.2139/ssrn.921591
|View full text |Cite
|
Sign up to set email alerts
|

Is Locking Domestic Funds into the Local Market Beneficial? Evidence from the Polish Pension Reforms

Abstract: This paper is concerned with the effect of enforced home bias on the development of emerging stock markets. It provides a detailed study of the impact on the Warsaw Stock Exchange of the Polish pension fund reforms and the associated restrictions on international investment. The time path of market development for the Warsaw Stock Exchange is compared with a benchmark sample consisting of the other seven post-communist countries that joined the EU in May 2004. It is shown that benefits arising from the pension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…In the only other study, directly related to ours, Zalewska (2006) analyzed the long-run effects of the pension reform in 1999 and found that the Polish stock market was performing worse than other emerging markets in the region afterwards. However, Zalewska (2006) did not investigate capital flows to the market, as we do in this paper, and could not assess their direct impact on stock prices in the short-run or in the long-run. The present investors' structure of the Polish stock market has its origin in the pension system reform in the year 1999, when the public system was enriched by a private component, represented by open-end pension funds.…”
Section: Institutional Investors Trading On Stock Marketsmentioning
confidence: 79%
See 1 more Smart Citation
“…In the only other study, directly related to ours, Zalewska (2006) analyzed the long-run effects of the pension reform in 1999 and found that the Polish stock market was performing worse than other emerging markets in the region afterwards. However, Zalewska (2006) did not investigate capital flows to the market, as we do in this paper, and could not assess their direct impact on stock prices in the short-run or in the long-run. The present investors' structure of the Polish stock market has its origin in the pension system reform in the year 1999, when the public system was enriched by a private component, represented by open-end pension funds.…”
Section: Institutional Investors Trading On Stock Marketsmentioning
confidence: 79%
“…The number of studies investigating emerging or smaller markets is still very limited. The short-run impact of institutional trades in multiple emerging markets has been documented by Domowitz et al (2001) in the context of trading costs and Chiyachantana et al (2004 and2006) who reported evidence about temporary spikes in price volatility during the trade execution periods. Charoenwong et al (2010) also found that large-sized trades account for a substantial impact on stock prices in Thailand.…”
Section: Institutional Investors Trading On Stock Marketsmentioning
confidence: 98%
“…Not surprisingly such a massive cash inflow had a strong impact on the WSE development and market characteristics. Zalewska (2005Zalewska ( , 2006 reports that in the case of many companies listed on the WSE the local pension funds have taken over 70-80% of their free float. The ratio of total value traded to market capitalisation in 2002-2003 was less than half of that observed in 1996-1997.…”
Section: Poland: Wigmentioning
confidence: 99%
“…There exists evidence for the Polish market about the stabilizing effect of pension funds, as a group of large institutional investors, on stock prices volatility, provided in Bohl and Brzeszczynski (2006) and Bohl, Brzeszczynski and Wilfling (2009). There is, however, rather limited research and very little empirical evidence available on the direct impact of trades performed by institutional investors on stock market returns in emerging and thinly traded markets, except that reported in Zalewska (2006). We contribute to filling this niche by using unique data about actual transfers of capital from the pension institute (ZUS), collected centrally from all employees in Poland, to private pension funds, which invest it in the financial market.…”
mentioning
confidence: 99%
“…private pension funds) on the stock market prices, in particular when their impact is viewed from the perspective of various time horizons, such as quarterly, monthly, weekly and daily. Zalewska (2006) analyzed the long-run effects of the pension reform in 1999 and found that the Polish stock market was performing worse than other emerging markets in the region afterwards. However, Zalewska (2006) did not investigate capital flows to the market, as we do 1 7 in this study, and could not assess their direct impact on stock prices in the short-run or in the long-run.…”
mentioning
confidence: 99%